Implementation of Religious Moderation Based on Inclusive Theology and Dialogue in Indonesia: Opportunities and Challenges - Fitriani, Fitriani; Nafrial, Nafrial; Sudarman, Sudarman; Jamaluddin, Wan; Syahril, Sulthan (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2024)
This research examines the importance of inclusive theology and dialogue between religious communities in supporting social harmony in multicultural societies, focusing on Indonesia. In the era of globalization, meetings between diverse religions and cultures are increasingly occurring, creating challenges and opportunities for mutual understanding. Inclusive theology, which recognizes religious diversity and seeks universal values ​​in those traditions, is proposed as an approach to encourage respect, dialogue, and cooperation between religious communities. This research uses a qualitative method that combines studies of interfaith initiatives, this research highlights the potential of inclusive theology to bridge differences and reduce tensions. This research also explores the role of education and social media in supporting inclusive theology through spreading messages of peace and coexistence. Research findings show that inclusive theology promotes religious tolerance and forms the basis for cooperation in the social, educational, and environmental fields. Despite the challenges of an exclusive theological perspective, continued efforts in education and the use of social media are essential to increasing broader acceptance. This research contributes to the discussion of religious pluralism by providing practical and theoretical insights into the application of inclusive theology to create peace and mutual understanding in diverse societies.